2020
DOI: 10.1093/jas/skaa168
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress-induced deficits in growth, metabolic efficiency, and cardiovascular function coincided with chronic systemic inflammation and hypercatecholaminemia in ractopamine-supplemented feedlot lambs

Abstract: Heat stress hinders growth and well-being in livestock, an effect that is perhaps exacerbated by the β1 agonist ractopamine. Heat stress deficits are mediated in part by reduced feed intake, but other mechanisms involved are less understood. Our objective was to determine the direct impact of heat stress on growth and well-being in ractopamine-supplemented feedlot lambs. Commercial wethers were fed under heat stress (40 °C) for 30 d, and controls (18 °C) were pair-fed. In a 2 × 2 factorial, lambs were also giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Several loci implicated (Wagner and Efrel, 2005). Additional data from this study demonstrated an inflammatory response due to HS that was moderated by RH (Swanson et al, 2020). Heat stress alone altered expression of two loci in adipose.…”
Section: Discussionmentioning
confidence: 54%
“…Several loci implicated (Wagner and Efrel, 2005). Additional data from this study demonstrated an inflammatory response due to HS that was moderated by RH (Swanson et al, 2020). Heat stress alone altered expression of two loci in adipose.…”
Section: Discussionmentioning
confidence: 54%
“…Others such as FOS and FOSB are associated with inflammation ( Wagner and Efrel, 2005 ). Additional data from this study demonstrated an inflammatory response due to HS that was moderated by RH ( Swanson et al, 2020 ). Heat stress alone altered expression of two loci in adipose.…”
Section: Discussionmentioning
confidence: 59%
“…Decreased FFA mobilization due to HS was possibly an effect of chronic exposure. In study 1, HS caused increased circulating epinephrine ( Swanson et al, 2020 ). If steers in study 2 responded likewise, it is reasonable to speculate that their βAR became desensitized and less responsive to epinephrine.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Sheep exposed to heat stress exhibit increased concentrations of plasma TNF-α, a key mediator of inflammation, and increased total white blood cell, monocyte, and granulocyte counts (40 °C for 12 h followed by 30 °C for 12 h for 30 days) [ 55 ]. Expression of proteins associated with the innate immune response, such as haptoglobin, heat shock protein 90-α (HSP90AA1), and the endoplasmic precursor (HSP90B1), is induced in heat-stressed pigs (constant 30 °C for 21 days) [ 56 ].…”
Section: What Components Of the Immune System Are Activated During Heat Stress?mentioning
confidence: 99%